Habitat suitability for chiru (Pantholops hodgsonii): Implications for conservation management across the Tibetan region of Chang Tang. Issue 3 (22nd January 2015) - Qi, Guilan; Hu, Yibo; Owens, Jacob R.; Dai, Qiang; Hou, Rong; Yang, Zhisong; Qi, Dunwu
ABSTRACT Understanding how population density relates to habitat underlies basic ecological theory and is pertinent to conservation issues. Chiru (Pantholops hodgsonii) are an endangered steppe‐dwelling ungulate endemic to the Tibetan plateau. To prepare effective conservation and management strategies for this species, we require detailed knowledge of the relationship between group size and habitat conditions. We surveyed the Chang Tang region of Tibet and used data collected along vehicular line transects to record the presence and group size of chiru. Using ecological niche factor analysis, we inferred the ecological requirements of chiru in relation to a large number of topographic, vegetation, and anthropogenic variables. We used these analyses to estimate habitat suitability models and describe their optimum range. Areas favored by chiru had moderate grazing by domestic animals, gentle slopes, and villages present only at lower altitudes. Chiru showed a high level of specialization regarding the presence of villages and gentle slopes, and were negatively associated with areas of those easily accessed by people. We suggest new management measures for the long‐term conservation of chiru. Specifically, we focus on the rehabilitation of natural plains for grazing by chiru, recognizing that conservation of large groups may require special efforts. For smaller groups and solitary chiru, the large tracts of unsuitable or marginal areas may expose them to different threats that could pose greater challenges for conservation management. © 2015 The Wildlife Society.